Keep your money, lose your “friend” : the moderating role of money in effects of social loneliness on anthropomorphism - Tan, Kian Leong (Nanyang Technological University, 2019)
One line of research suggests that when people feel lonely, they may engage in anthropomorphic processes to satisfy their need to create social connection. Another line of research suggests that when people think about money, they become more self-reliant, which reduces their need to create social connection. The present research aims to examine the intersection where these two lines of research meet. Specifically, the present studies investigated how social loneliness may elicit anthropomorphic tendencies, and how this causal relationship may be moderated by the thinking about money. In this paper, two hypotheses were tested: Hypothesis 1: Participants who recalled social exclusion (vs. disappointment) experience would show a stronger tendency to anthropomorphize non-animated objects, and Hypothesis 2) Participants who recalled social exclusion (vs. disappointment) experience would show a stronger tendency to anthropomorphize non-animated objects, and this causal relationship would be moderated by unscrambling money-related (vs. neutral) content. However, both hypotheses were not supported in the present research. Possible explanation and future directions were discussed.